Seed to plant transmission of Xanthomonas campestris pv. vignicola isolates in cowpea - Okechukwu, R.U.; Ekpo, E.J.A.; Okechukwu, O.C. (2010)
Seed transmission of Xanthomonas campestris pv. vignicola was investigated to ascertain the importance of seed as a primary source of inoculum for bacterial blight disease in cowpea. The study was carried out using seeds of five cowpea varieties (TVx 12349, IT86D-721, IT82D-889, Ife Brown and TVx 3236) artificially inoculated with three bacterial isolates (Ikenne, Kano and Ibadan), and seeds harvested from infected plants. Results showed that seed to plant transmission caused 6 – 24% post-emergence seedling mortality and 26 – 49% incidence of blight in plants raised from infected seeds. These results support seed transmission of X. campestris pv. vignicola in cowpea and suggest that the distant spread of bacterial blight on cowpea may also be due to seed transmission.